Statistical Experimental Design for the Extraction of Ti(IV) in the Ti(IV)-SO42- (H+, Na+) – Cyanex 301 – Kerosene – 5% (v/v) Heptane-1-ol System (Journal of Scientific Research, 2018)
The titled system has been investigated from the modelling point of view. The equilibration time for the system is 45 min, and 5% (v/v) heptane-1-ol in the organic phase is used as a  de-emulsifier. The factors affecting the extent of extractions are [Ti(IV)], pH(eq), [Cyanex 301], [SO42-] and temperature (T). The selected levels are high (+) and low (-) for these factors in the present investigation. Model equation for the extraction of Ti(IV) by Cyanex 301 is determined from 25 full factorial design. However, the success of the factorial design depends on the linear relationship between yield and factor. Plots of log CD vs log [Ti(IV)], pH(eq), log [Cyanex 301] and log [SO42-] are curves. Logistic functions involving these factors are considered in designing. While [Ti(IV)] < 1.00 g/L and [HA](o) > 0.10 mol/L, considered logistic functions viz. -log(1+316.2 ([Ti(IV)], mol/L)), -log (10-pH + 229 ´10-2pH), log ([HA](o), mol/L), -log (1+0.79 ([SO42-], mol/L)) and absolute temperature are abbreviated as M, P, E, S and T, respectively. Model is log CD = 5.847 + 0.964 M + 0.909 P + 2 E + 0.995 S – (1437.5/T). The experimental model illustrates that there is no interaction effect between the factors under investigation.